Stress and Coping Measures among Patients with Coronary Artery Disease in a Cardiac Hospital, Kathmandu - Saki, Kamala; Dangol, Bhuwan Kumari (Curriculum Development Journal, 2023)
Coronary Artery Disease (CAD) is the leading cause of death worldwide. Patients diagnosed with CAD face major physical and emotional challenges. Identifying stress among CAD patients can reduce the negative effects of illness perception, decrease adherence and complications by preventing numerous morbidities. The objective of study was to assess the stress levels and coping measures among CAD patients. A descriptive cross-sectional study design was chosen. Non-probability purposive sampling method was used to collect data among 376 CAD patients from outpatient department of Manmohan Cardiothoracic vascular and Transplant Center (MCVTC). Data was collected from 7th August to 9th September 2022, through a structured interview questionnaire using standardized tools consisting of the Perceived Stress Scale and Brief Cope scale. Data analysis was done using SPSS version 16, through descriptive statistics, and inferential statistics tests. In this study, 1.1% of CAD patients had low stress, 90.7% had moderate stress, and 8.2% had severe stress. Regarding coping measures, the most used coping measures were problem-focused coping measures with a median percent (75%) and 96.3% of CAD patients adopted adaptive coping. While there was a statistically significant between stress and duration of illness (p=.009) and frequency of hospitalization (p=.049) overall coping had a positive correlation with stress (r=0.157, p=.002). This study concluded that a moderate level of stress was prevalent among majority of CAD patients. Improving coping measures can help CAD patients to minimize stress. Thus, finding suggest that health personnel need to address coping measures to overcome from stress among CAD patients.